FASHION BRANDING STRATEGY TO ENCOURAGE ONLINE STORE PATRONAGE INTENTION - Burhanudin Burhanudin; Diva Eriel Noviza (Institute of Research and Community Outreach - Petra Christian University, 2023)
Companies are developing their brand image to drive online store patronage intention. Online store patronage intention is crucial in marketing as it shows consumers’ willingness to buy product in the online store and recommend the store to other consumers. However, it is currently unclear how brand image drives online store patronage intention in the context of fashion as well as the mediating variables in this relationship. This study aims to examine the influence of brand image on online store patronage intention directly and indirectly through customer perceived value and customer satisfaction. This study conducted a survey to test the proposed relationships. There were 221 respondents participating in the survey. To analyze the data, this study employed a structural equation modeling approach by evaluating the measurement model, followed by an evaluation of the structural model. This study found brand image affects online store patronage intention directly and indirectly through customer perceived value and customer satisfaction.